Implementing energy management system to increase energy efficiency in manufacturing companies - Javied, Tallal; Rackow, Tobias; Franke, Jörg (Procedia CIRP, 2015)
One of the main pillars of the modern industry is the uninterrupted supply of energy with a reasonable price. The energy production is based mostly on non-renewable energy resources that are getting more expensive progressively. This increase in energy cost consequently leads the companies to a more expensive production of goods. Therefore it has been established that energy efficiency is not only very important for the environment but also for the sustainable production in the manufacturing companies. Effective energy management plays an important role in the necessary increase of energy efficiency in industry. Next to the expansion of regenerative energies, it establishes a further pillar at closing the energy supply gap resulting from the energy transition. This paper presents the current energy situation in Germany and its impact on the German industry. Furthermore this paper presents a methodology which can be used by organizations to systematically implement energy management system. Eventually the paper provides a model that illustrates the realization of a PDCA cycle which is necessary for energy management in the organization.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Energy efficiency; Energy management; Organization structure; Sustainability